ANALISIS EVALUASI KOORDINASI SISTEM PROTEKSI ARUS LEBIH PADA SWITCHGEAR PLTP PT GEO DIPA ENERGI (PERSERO) - Haidar Nabil Muflih; Candra Febri Nugraha (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The electrical protection system in power generation is essential for ensuring reliability and operational continuity. Each protection device has specific settings and operating times, tailored to the protected zones and the types of disturbances that may occur. This research focuses on the analysis and evaluation of protection coordination in the 19 kV switchgear of Geothermal Power Plant Unit 1, operated by PT Geo Dipa Energi (Persero) in Dieng. The objective of this study is to verify the conformity of the existing settings with standards and coordination principles. The analysis is conducted through setting calculations and short-circuit simulations based on data from relay configuration tests under existing conditions. If the existing settings for overcurrent relays do not meet the standards, a resetting process will be carried out using calculations in line with the standards. The resetting of overcurrent relays includes determining pickup current, instantaneous trip settings, and time dial settings to ensure that the grading time between protection system components meets the standards. The results of this study indicate that there are overcurrent relay settings that still do not comply with the standards. After the relay settings have been reset, the analysis shows that the protection system can coordinate effectively in accordance with the standards.